Pengembangan Sistem Informasi Pemasaran pada Cv. Rumah Vera - Hartono, Sugiarto (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Evolving information technology can make business processes, which are carried out traditionally, transformed through the application of information technology that is useful for companies. Effective information systems design, should be used and provide a positive influence for the benefit of the organization. CV. Rumah Vera is a company that is engaged in the business of selling and marketing the property. The company began to realize that the implementation of information systems is very important in the development of its business. Rumah Vera requires a system that utilizes information technology, which can record all business transactions related to the marketing information system. Design methodology used is Agile methodology with object-oriented approach.